2021
DOI: 10.14393/bj-v37n0a2021-54149
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between intake values observed and predicted by nutritional systems for confined nellore cattle

Abstract: This study compared the dry matter intake (DMI) of Nellore heifers and bulls in the feedlot, predicted by the BR-Corte (2010 and 2016) and NRC (2000) nutritional systems. Hence, two experiments were conducted in a completely randomized design. The first one used 47 Nellore bulls, not castrated, with an average initial weight of 413 kg, and 19 months of age. The second experiment used 24 Nellore heifers with an average initial weight of 300 kg and 23 months of age. The accuracy and approximation of the DMI esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…where BW 0.75 = average metabolic body weight (kg) and ADG = average daily gain (kg/d). Ferreira et al (2021) evaluated DMI prediction models by BR-CORTE (Azevêdo et al, 2010 and2016) and NRC (2000) nutritional systems, with 47 feedlot Nellore cattle, bulls, the average initial body weight of 413 kg and 19 months of age. They concluded that the BR-CORTE model (Azevêdo et al, 2016) was more precise to predict DMI of Nellore cattle.…”
Section: State Of the Art On Dry Matter Intake Predictionmentioning
confidence: 99%
“…where BW 0.75 = average metabolic body weight (kg) and ADG = average daily gain (kg/d). Ferreira et al (2021) evaluated DMI prediction models by BR-CORTE (Azevêdo et al, 2010 and2016) and NRC (2000) nutritional systems, with 47 feedlot Nellore cattle, bulls, the average initial body weight of 413 kg and 19 months of age. They concluded that the BR-CORTE model (Azevêdo et al, 2016) was more precise to predict DMI of Nellore cattle.…”
Section: State Of the Art On Dry Matter Intake Predictionmentioning
confidence: 99%